Release of KSUZ 0802 Zoysiagrass - J. Fry; Ambika Chandra (Kansas Agricultural Experiment Station Research Reports, 2016)
A new zoysiagrass cultivar, under the experimental designation KSUZ 0802, was released jointly by the Kansas Agricultural Experiment Station and Texas A&M AgriLife Research in 2015.
Keywords: cultivar development; turfgrass; warm-season grasses